Evangelium: Gud er nær: Det epokegørende budskab om sejr i kampen og fornyelse af kulten - Nielsen, Jesper Tang (Dansk Teologisk Tidsskrift, 2024)
Abstract: Morten Hørning Jensen’s higher doctoral dissertation (habilitation) The ‘Gospel’ Between Emperor and Temple in the Gospel of Mark is a meticulous investigation of the Greek root εὐαγγελ- and the Hebrew equivalent בשׂר in Greek and Hebrew literature before the Gospel of Mark and Mark’s use of the term in his text. Hørning Jensen concludes that the story of Jesus is the gospel to Mark “since Jesus, through his life, death, and resurrection, re-establishes covenantal community with and proximity to the God through kingly victory and temple-cultic renewal” (462). This way of understanding εὐαγγέλιον places it in direct continuity with Deutero-Isaiah, who uses the word to designate the return of Yahweh to Zion.The review article summarizes the argument at length, then poses some critical questions and finally offers a more substantial criticism of the fact that Paul is left out of the interpretation and only figures as a “test case” for the meaning of εὐαγγέλιον in Second Temple Judaism. If the relation to Paul is taken into account, the Gospel of Mark should be conceived of as a narrative unfolding of Paul’s gospel and not as the story of Jesus on the basis of the visions of Isaiah. One wonders why the author does not see a relation between Paul and Mark. The reason may be that he has sympathy for Papias’ idea that Mark was interpreter of Peter, which might make it virtually impossible for him to be influenced by Paul.